ULAMA DI PERSIMPANGAN JALAN (Telaah Terhadap Peran Ulama dalam Kehidupan Politik di Indonesia) - Muh. Haras Rasyid (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2020)
Ulama at the crossroads, examine the role of Ulama in political life in Indonesia. Ulama the title on a personal figure who has advantages in Islam, especially religious knowledge, practice of worship and akhlaq al karimah. Ulama are actually located at a crossroads as neutral position for enlightenment protector and guidance to the people. However, the condition of politics in Indonesia, some Ulama are no longer in an ideal position that exists at a crossroads regulating flow interests of the people, but they also put themselves on political practice. Every children of Indonesian has the same rights to play role on the nation interest, especially through the realm of politics. Including Ulama as one of the nation component is not restricted to participate on contributing in the interests of the nation and state according to their expertise. It's just that their wisdom is needed to not get involved on negative things but the contrary give colour of Islam on Indonesian politic for real.